A Debreceni Kossuth Lajos Tudományegyetem archontológiája 1950-1990 V. rész - Mudrák, József (Gerundium, 2016)
THE ARCHONTOLOGY OF LAJOS KOSSUTH UNIVERSITY OF ARTS AND SCIENCES, PART V: INSTITUTE OF CHEMISTRY (1950–1990). he Archontology of Kossuth University for the School of Arts, the School of Sciences, and for the So-Called ”Central Units” between January 1, 1950, and December 31, 1990, was compiled on the basis of the personal cards and personal iles of the Personnel Department of the Rector’s Oice, and the scantily documented section for the 1950s was supplemented from the annually arranged documentary material of the Personnel Oice. Even so, however, the existing material fails to be complete. It is impossible to compile the archontology with perfect accuracy. Part V introduces the updated lists of the teaching and non-teaching staf of the Department of Chemistry, School of Sciences, from institute director to janitor.